Pengaruh Kepemimpinan Transformasional Terhadap Kepuasan Kerja Karyawan Dimediasi Oleh Keadilan Organisasi Pada RSIA Cahaya Bunda Cirebon - Sylvani Sylvani; Ali Jufri; Sari Laelatul Qodriah (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2020)
ABSTRACT Health in the modern era is now an inseparable necessity from the development of healthy and smart Indonesian people. Hospitals as one of the health facilities that provide health services to the community have a very strategic role in accelerating the improvement of community health status. Therefore, hospitals are required to provide quality services in accordance with established standards and can reach all levels of society. For this reason, the need for synergy between leaders and employees. Employees still complain about the way leaders handle each employee's complaints, such as complaints of discrepancies between salaries and work performed, employees still feel discriminated in the sense of being discriminated according to social status, the length of the process of determining to become permanent employees, and so forth. From the factors mentioned above that the role of the leader in leading must be wise and fair both for the organization and employees in the organization. This study aims to obtain empirical evidence of whether or not the influence of transformational leadership on job satisfaction is mediated by organizational justice. This study used a correlational quantitative method and the data processing was assisted with SPSS 22. The population of this study was all employees of RSIA Cahaya Bunda including permanent employees and contract employees while the study sample was only 127 permanent employees. Determination of samples using Slovin formula. The results of this study indicate that transformational leadership has a direct positive effect on job satisfaction, organizational justice has a positive effect on job satisfaction, transformational leadership has a positive effect on organizational justice and organizational justice is able to mediate the relationship between transformational leadership and job satisfaction. Keywords: transformational leadership, job satisfaction, organizational justice, hospital.